Genus- Homoeothrix (Thuret) Kirchner (Cyanophyceae) from Hartala Lake, Maharashtra - A. K. Jawale2, J. S. Dhande1* and (Journal of Experimental Sciences, 2011)
While exploring algal flora of Hartala lake (latitude 210 00Ã¢â‚¬â„¢20.56Ã¢â‚¬Â north and longitudes 760 01Ã¢â‚¬â„¢31.31Ã¢â‚¬Â east), District Jalgaon (M.S.) 84 taxa of cyanophyceae were collected. Present communication deals with five taxa of Homoeothrix. Of these Homoeothrix nordstedtii (Born. et Flah.) Komarek et Kann, Homoeothrix varians Geitl. and Homoeothrix varians Geitl. var. major Geitl. are first time reported from India.